Pollen Stoichiometry May Influence Detrital Terrestrial and Aquatic Food Webs - Filipiak, Michał (Frontiers in Ecology and Evolution, 2016)
Pollen rains may temporally mitigate nutritional limitations experienced by terrestrial and aquatic detritivores by supplying stoichiometrically balanced food during periods of detritivore growth and development (spring-summer). This may affect the functioning of food webs and thus influence fundamental processes, e.g., by enabling fungi to decompose nutritionally scarce litter. Nutritional limitation may be studied within the framework of ecological stoichiometry by comparing the stoichiometric mismatches experienced by organisms feeding on various foods. To this end, the elemental compositions of pine pollen, litter and detritivores (fungi, protozoans, worms, insects, mites, millipedes, isopods and slugs) were compared, as were the stoichiometric mismatches experienced by the detritivores feeding on litter and pollen. Additionally, the contribution of pollen to the nutrient flow from the land to aquatic ecosystems was estimated through a literature review. Compared to litter, pine pollen is a stoichiometrically well-balanced food source in terms of its C:N:P ratio but also because of its high concentrations of K, S and Cu and its favorable Zn:Fe ratio. This characteristic is especially suitable to fungi, which may be responsible for the redistribution of pollen-derived nutrients in food webs, particularly aquatic ones. Pollen rains of various plant species act as temporal pulses of nutrients that are rapidly utilized and quickly introduced into the food web, so calculations of annual biomass input may be misleading. Pollen is an easily available, digestible and nutritious food for fungi, bacteria, protozoans and various groups of invertebrates, which suggests that pollen plays an important role in within- and cross-ecosystem nutrient cycling.